Clever Girl Finance : Learn How Investing Works, Grow Your Money - Sokunbi, Bola, 1981- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2021)
Many young women today lack the financial literacy resources that speak to their demographic and lack the support to leverage their earnings to build real wealth. This lack of knowledge causes this demographic to be in the group of least likely to invest and build long term wealth despite graduating college and opening businesses at record numbers. They are earning money but need the skills to grow it long term. This book will provide them with foundational investing skills, as well as introduce them to examples of women like them who have built wealth through investing, making the topic more attractive/approach and in away that's relatable to them.
Includes index.
Keywords: Women -- Finance, Personal; Investments